Is there a relationship between surgical case volume and mortality in congenital heart disease services? A rapid evidence review. Issue 12 (18th December 2015) - Preston, L; Turner, J; Booth, A; O'Keeffe, C; Campbell, F; Jesurasa, A; Cooper, K; Goyder, E
Abstract : Objective: To identify and synthesise the evidence on the relationship between surgical volume and patient outcomes for adults and children with congenital heart disease. Design: Evidence synthesis of interventional and observational studies. Data sources: MEDLINE, EMBASE, CINAHL, Cochrane Library and Web of Science (2009–2014) and citation searching, reference lists and recommendations from stakeholders (2003–2014) were used to identify evidence. Study selection: Quantitative observational and interventional studies with information on volume of surgical procedures and patient outcomes were included. Results: 31 of the 34 papers identified (91.2%) included only paediatric patients. 25 (73.5%) investigated the relationship between volume and mortality, 7 (20.6%) mortality and other outcomes and 2 (5.9%) non-mortality outcomes only. 88.2% were from the US, 97% were multicentre studies and all were retrospective observational studies. 20 studies (58.8%) included all congenital heart disease conditions and 14 (41.2%) single conditions or procedures. No UK studies were identified. Most studies showed a relationship between volume and outcome but this relationship was not consistent. The relationship was stronger for single complex conditions or procedures. We found limited evidence about the impact of volume on non-mortality outcomes. A mixed picture emerged revealing a range of factors, in addition to volume, that influence outcome including condition severity, individual centre and surgeon effects and clinical advances over time. Conclusions: The heterogeneity of findings from observational studies suggests that, while a relationship between volume and outcome exists, this is unlikely to be a simple, independent and directly causal relationship. The effect of volume on outcome relative to the effect of other, as yet undetermined, health system factors remains a complex and unresolved research question.